The Stinky Cheese Man and Other Fairly Stupid Tales - Jon Scieszka (London, United Kingdom Penguin Books Ltd, 1998)
d
Keywords: Circle Time Book - Fractured Fairy Tales -- Circle Time Book - Fractured Fairy Tales